Karamanlıca Bir Zebur'da Yapı Bakımından Devrik Cümleler - Kahya, Hayrullah (Muş Alparslan Üniversitesi, 2017)
In almost all Turkish grammar books the term of anacoluthon has been described as a kind of sentence whose predicate located in the first or middle of the sentence. This kind of sentence, anacoluthon, is usually used in colloquial speech and some specific texts have colloquial speech. There are anacoluthons in every period of Turkish language history. They are rare in Kokturk Turkish, but they began to increase from period of Old Uighur Turkish. In Turkey Turkish, after Turkish Language Revolution, especially Nurullah Atac (1898-1957), a famous author in Turkish literature, consciously made an effort that they began to increase comparatively in written language of Turkish. In current study, I analyzed anacoluthons in two main categories in a Psalm book written in Turkish with Greece alphabet, which means Karamanlidika. First part consists of anacoluthons which have only one element after predicate. The second part consists of anacoluthons which have multiple elements after predicate. Most of anacoluthons in the text have the same structure in other Turkish texts. However, in the Psalm, frequency of the sentences having multiple elements after predicate is more dominant than other untranslated Turkish texts. Additionaly, it has been looked that some of the anacoluthons in the text have some effect of the Greek grammatical structure.

Hemen hemen tüm dilbilgisi kitaplarında “yüklemi sonda olmayan cümle” şeklinde tanımlanan devrik -kimi kaynaklarda kuralsız- cümle, daha çok konuşma dilinde ve konuşma diline yakın bir dille yazılmış metinlerde görülür. Devrik cümleye Türk dili tarihinin her döneminde az çok rastlanmaktadır. Köktürkçede nadiren görülen devrik cümleler, Eski Uygur Türkçesi döneminden itibaren dilimizde daha sık görülmektedir. Türkiye Türkçesinde ise devrik cümle, Dil Devrimi’nden sonra Nurullah Ataç (1898-1957) gibi yazarların bilinçli gayretleriyle yazı dilinde tekrar canlanmaya başlamıştır.Bu çalışmada Grek harfli Türkçe (Karamanlıca) ile yazılmış bir Zebur (Psaltrion)’da geçen devrik cümleler, yapıları bakımından incelenmiştir. Çalışmada devrik cümleler, yüklemden sonra tek ögenin bulunduğu devrik cümleler, yüklemden sonra birden çok ögenin bulunduğu cümleler olmak üzere ikiye ayrılarak incelenmiştir. İncelediğimiz metindeki devrik cümlelerin çoğu Türkçe diğer metinlerde de rastlanabilecek yapıdadır. Yüklemden sonra birden çok ögenin geldiği cümle oranı telif Türkçe metinlere göre nispeten fazladır. Bazı devrik yapıların ise Yunancanın etkisini taşıdığı görülmektedir.
Anacoluthons in a Karamanlidika Psalm in Terms of Structure
anemon
Keywords: Anacoluthon; Syntax; Karamanlidika; Psalm; Karamanlides; Karamanlıca; Zebur; Devrik Cümle; Söz Dizimi; Karamanlılar